KEARIFAN LOKAL MASYARAKAT DESA MBAWA DALAM MEWUJUDKAN TOLERANSI BERAGAMA - I Made Purna (Jurnal Pendidikan dan Kebudayaan, 2016)
Donggo is an ethnic community living in Mbawa Village, District Donggo, Bima, West Nusa Tenggara. This Ethnic consists of various monotheism religions, such as Islam, Catholic, and Protestant. Despite having a plural society background from various religions, Donggo’s community in Mbawa village have capability in maintaining the harmony among their community. This study aims to analyze how the community in Mbawa village with various religions can avoid religious-based conflict. In addition, it analyzes what strategies are used to achieve the harmony among the community of Mbawa village. Observation was used as the main method of this study. The results of this study shows that in maintaining harmony among religious people in their community, people of Mbawa village apply their local knowledge as a cultural strategy to avoid religious conflict. In summary, local wisdom in Mbawa Village can bridge the community members of different religious beliefs.